ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI NILAI TUKAR RUPIAH ATAS DOLAR AMERIKA SERIKAT DI INDONESIA - Diana, I Kadek Arya; Dewi, Ni Putu Martini (E-Jurnal Ekonomi Pembangunan Universitas Udayana, 2020)
Changes in economic activity are usually reflected in changes or fluctuations in currency exchange rates. Indonesia is a country that adopts an open economic system, with the adoption of a free floating exchange rate system since August 1997. This study aims to analyze the effect of interest rates, money supply, inflation, and exports simultaneously and partially on the Rupiah exchange rate over the United States Dollar period 2010-2018. The data used in this study are secondary data. The analysis technique in this research is multiple linear regression. The results of this study indicate that simultaneous variable interest rates, money supply, inflation, and exports have a significant effect on the Rupiah exchange rate against the United States Dollar. Partially, the interest rate variable has a positive effect on the Rupiah exchange rate against the US Dollar, while the variable money supply, inflation, and exports have no effect on the Rupiah exchange rate against the US Dollar. In this analysis shows that the variable that has a dominant influence on the Rupiah exchange rate against the United States Dollar is the variable money supply Keywords: interest rates, money supply, inflation, exports, Rupiah exchange rate against the United States Dollar